Experimental study on concrete of blended cement with eggshell powder and fly ash - Wong, Johnny Ren Xiang (2018)
Cement as a vital material of concrete production plays an important role in construction field. However, production of cement had brought severe negative impact to environment. Research found that there is approximately 780 kg of carbon dioxide (CO2) is emitted to atmosphere for every ton of cement produced. In order to minimize the negative effect of cement production, alternative environmental friendly material should be determined. In the past decade, consumer waste and industrial by-product handling method always become an environmental issue. Disposal of egg shells through landfilling might detrimental to human health as it may become the habitat for vermin. Fly ash as industrial by product had led to severe disposal and leachate problem also. Recent researches have proposed that these waste materials can be recycled and added to concrete as an effort to minimize post-consumer wastes and industrial by-products entering the landfills. Egg shells riches in pure form of calcium carbonate (CaCO3) which is nearly similar as composition of limestone. The composition of fly ash includes substantial amounts of silicon dioxide (SiO2), aluminium oxide (Al2O3) and calcium oxide (CaO). When they mix with Portland cement and water, it will result in production of calcium-silicates hydrates (C-S-H) which primarily responsible for the strength of concrete. As there is potential of developing these waste product as construction material, investigation is conducted to determine the mechanical properties and optimum mix design of blended cement with egg shells powder and fly ash. In this investigation, a combination of 30% of fly ash and four different percentages of eggshell powder with respect to cement were added into the concrete mix of Grade M30. The materials used in this experimental study involved non-composite Portland cement, coarse aggregate, fine aggregate, sand, Class C fly ash and eggshell powder. From the investigation, all the casted concrete has achieved the designated compressive strength of 30MPa. 30% of fly ash and 5% of eggshell powder is the optimum dosage for concrete to achieve higher flexural strength. Besides, the splitting tensile strength of concrete decrease with the further increase in proportion of fly ash and eggshell powder.